Using a quantum well heterostructure to study the longitudinal and transverse electric field components of a strongly focused laser beam - Malzer, Stefan; Leuchs, Gerd; et al. (Journal of Applied Physics, 2006)
We report a method to measure the electric energy density of longitudinal and transverse electric field components of strongly focused polarized laser beams. We used a quantum well photodetector and exploited the polarization dependent optical transitions of light holes and heavy holes to probe the electric field distribution in the focal region. A comparison of the measured photocurrent spectra for radially and azimuthally polarized beams at the light and heavy hole absorption peaks provides a measure of the amount of the longitudinal electric field component. © 2006 American Institute of Physics.